2016
DOI: 10.1182/blood-2016-02-696757
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of nodal marginal zone lymphoma

Abstract: Key Points• PTPRD lesions are among the most recurrent alterations in NMZL and appear to be enriched in this lymphoma type across mature B-cell tumors.• NMZL and SMZL genetics overlap with the exceptions of PTPRD lesions, supporting their distinction as independent entities.Nodal marginal zone lymphoma (NMZL) is a rare, indolent B-cell tumor that is distinguished from splenic marginal zone lymphoma (SMZL) by the different pattern of dissemination. NMZL still lacks distinct markers and remains orphan of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
125
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 69 publications
12
125
3
Order By: Relevance
“…In NMZL, the occurring mutations are responsible for the removal of the entire gene or the tyrosine phosphatase portion of its protein and exert their lymphomagenetic action in a STAT3-independent manner. On these grounds the almost exclusive, although not constant, occurrence of mutations in PTPRD gene further support the view of keeping separate NMZL from other types of marginal zone lymphomas [45].…”
Section: Genetic Profilesupporting
confidence: 55%
See 1 more Smart Citation
“…In NMZL, the occurring mutations are responsible for the removal of the entire gene or the tyrosine phosphatase portion of its protein and exert their lymphomagenetic action in a STAT3-independent manner. On these grounds the almost exclusive, although not constant, occurrence of mutations in PTPRD gene further support the view of keeping separate NMZL from other types of marginal zone lymphomas [45].…”
Section: Genetic Profilesupporting
confidence: 55%
“…With the exception of MLL2, which is present in more than one third of cases, the other affected genes occur in about 20% of cases. Notably, PTPRD is mutated in 20% on these patients and this defect seems restricted to NMZL across mature B-cell tumors [45]. PTPRD appears a critical molecule since it is a receptor-type protein tyrosine phosphatase known to regulate cell growth and behaves like a tumor suppressor.…”
Section: Genetic Profilementioning
confidence: 99%
“…The mutation profile of NMZL as shown by WES is similar to that of SMZL (Table ). KLF2 mutation is found in 17% of NMZLs . Mutation in the NOTCH signalling pathway involves mainly NOTCH2 (20%), SPEN (11%) and RBPJL (6%), and these mutations are seen overall in 40% of NMZLs, whilst mutation in the NF‐κB signalling pathway mainly involves TNFAIP3 (14%), BCL10 (11%), CARD11 (8%), BIRC3 (6%) and TRAF3 (6%), and is observed in 50% of cases .…”
Section: Marginal Zone Lymphomasmentioning
confidence: 99%
“…Deep sequencing of nodal MZL patients found that 5/35 (14%) cases had a mutation in the adhesion receptor ADGRV1 (also known as GPR98) and the cadherin receptors CELSR1, CELSR2 and CELSR3 were each mutated in 2/35 (6%) cases [183]. In addition to mutation, t(X;14) translocations causing upregulation of purinergic receptor GPR34 were observed in 2/61 (3%) cases of MALT, 1/43 (2%) cases of nodal MZL and 1/19 (5%) cases of extranodal DLBCL [184].…”
Section: Marginal Zone Lymphomamentioning
confidence: 99%
“…Exome sequencing found 2/35 (6%) cases of MZL had a mutation in CXCR4 [183] and the CXCR4 WHIM mutation was found in 1/20 (5%) MZL patients [192]. A significant correlation has been observed between CXCR4 expression and bone marrow involvement and loss of CXCR4 expression combined with upregulation of CXCR7 has been suggested to correlate with MALT progression to DLBCL [173].…”
Section: Marginal Zone Lymphomamentioning
confidence: 99%